Role of immune dysregulation in peri-implantitis - Huang, Mingshu; Wang, Chao; Li, Ping; Lu, Hongye; Li, An; Xu, Shulan (Frontiers in Immunology, 2024)
Peri-implantitis, a complex condition that can lead to dental implant failure, is characterized by inflammatory destruction resulting from immune dysregulation. Oral microbial dysbiosis and foreign body stimulation are the main factors contributing to such dysregulation, impairing immune cell function and triggering an inflammatory response. Immune dysregulation plays a critical role in the pathophysiology of peri-implantitis, impacting the balance of T cell subsets, the production of inflammatory factors, and immune-related molecular signaling pathways. Understanding the relationship between immune dysregulation and peri-implantitis is crucial for developing targeted strategies for clinical diagnosis and individualized treatment planning. This review explores the similarities and differences in the immune microenvironment of oral bacterial infections and foreign body rejection, analyzes the relevant molecular signaling pathways, and identifies new key targets for developing innovative immunotherapeutic drugs and effective and personalized treatment modalities for peri-implantitis. Additionally, it addresses the challenges and potential directions for translating immunotherapy into clinical practice for peri-implantitis, offering insights that bridge the gaps in current literature and pave the way for future research.